Refractory coeliac disease: or is it? - Amadi, Chidi (BMJ Case Rep, 2017)
A previously healthy 33-year-old man presented with a 3-month history of nausea, anorexia and weight loss. Coeliac disease was diagnosed at another hospital with positive serology and D2 biopsies and he was started on a gluten-free diet. The details of these tests were not available to us. Despite good adherence to a gluten-free diet, he continued to lose weight and became anaemic. A repeat gastroscopy showed D2 ulcers. Helicobacter pylori infection was excluded, coeliac serology remained negative but D2 biopsies showed partial duodenal villous flattening with intraepithelial lymphocytosis. Type 1 refractory coeliac disease was diagnosed. Prednisolone and azathioprine were commenced but the vomiting and weight loss progressed. A subsequent gastroscopy and CT scan revealed a D3 stricture and duodenal dilatation, respectively, in keeping with superior mesenteric artery syndrome. An infracolic duodenojejunostomy was performed and immunosuppression stopped. Subsequently, all his symptoms resolved and he remains well on a gluten-free diet.